Cultivating admiration in brands: Warmth, competence, and landing in the “golden quadrant” - Aaker, Jennifer L.; Garbinsky, Emily N.; Vohs, Kathleen D. (Journal of Consumer Psychology, 2012)
AbstractAlthough a substantial amount of research has examined the constructs of warmth and competence, far less has examined how these constructs develop and what benefits may accrue when warmth and competence are cultivated. Yet there are positive consequences, both emotional and behavioral, that are likely to occur when brands hold perceptions of both. In this paper, we shed light on when and how warmth and competence are jointly promoted in brands, and why these reputations matter.